(untitled) (International Journal of Engineering and Computer Science, 2015)
This paper proposes a novel simplified model of a photovoltaic module and also the modeling of hourly cloudless solar radiation of a particular site to achieve optimal operation. This model uses standard specifications along with actual solar radiation and temperature. This proposed work develops a matlab/simulink model to generate simulation of solar radiation of any location to provide the insolation on a photovoltaic module of any orientation and for any time of the year. A single diode model for current voltage characteristics and maximum power operation of a photovoltaic module is also presented which models the effect on VI characteristics of varying climate conditions. The combined model of solar radiation and PV module provide a tool to investigate the effect of meteorological conditions on the performance of a PV module generator. The predicted solar radiation and the experimental data are in good compliance.